2006
DOI: 10.1016/j.susc.2005.10.066
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical response function of a compressed lithium monolayer

Abstract: Since recent both theoretical and experimental results have proved that the simple behaviour light alkaline metals present at equilibrium breaks when high pressures are applied, they have become an important object of study in Condensed Matter Physics. On the other hand, development of new techniques in the atomic manipulation allows the growth of atomic monolayers (ML's), therefore rising the interest to analyze low dimensional systems under different conditions. In particular, new ab initio calculations perf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Shockley surface states existing at the (1 1 1) surfaces of noble metals [56,149,[366][367][368][369][370][371][372][373][374] support this collective excitation, which owes its existence to the spatial coexistence of a 2DEG with a 3D electron gas. In Ag the excitation is ascribed to the screening of the Shockley surface states electrons by bulk electrons [367,375], while recent results have indicated that in both Au [150] and Cu [376] the opposite phenomenon occurs: slow bulk electrons are screened by the faster surface state electrons.…”
Section: Predictions Of Asp In (1 1 1)-oriented Ag Filmsmentioning
confidence: 81%
“…Shockley surface states existing at the (1 1 1) surfaces of noble metals [56,149,[366][367][368][369][370][371][372][373][374] support this collective excitation, which owes its existence to the spatial coexistence of a 2DEG with a 3D electron gas. In Ag the excitation is ascribed to the screening of the Shockley surface states electrons by bulk electrons [367,375], while recent results have indicated that in both Au [150] and Cu [376] the opposite phenomenon occurs: slow bulk electrons are screened by the faster surface state electrons.…”
Section: Predictions Of Asp In (1 1 1)-oriented Ag Filmsmentioning
confidence: 81%
“…[59][60][61][62][63][64][65][66][67] One can see in Fig. 6 that surface excitation spectra evaluated in the jellium model are rather featureless in this low-energy domain compared to Fig.…”
Section: Calculation Results and Discussionmentioning
confidence: 92%